Validitas Konstruk Ikhlas: Analisis Faktor Eksploratori terhadap Instrumen Skala Ikhlas - Lu’luatul Chizanah; M. Noor Rochman Hadjam (Faculty of Psychology, Universitas Gadjah Mada, 2011)
In this study, the construct validity of ikhlas was examined. Exploratory factor analysis was conducted and followed with testing the correlation among the factors of ikhlas, metaneeds, and altruism. The subjects in this study amounted to 205 people who participated in the fulfilling scale. The results show that the construct of ikhlas consists of four dimensions i.e transcendental motives, emotional control, superiority feeling, and conception as the Servant of God. Emotionalcontrol is a region that overlaps with metaneeds and altruism. This indicates that the construct of ikhlas has some areas that overlap with the other constructs, but rather as a whole, it still can be saidthat there is a unique region described by ikhlas.